ILC2s Induce Adaptive Th2-Type Immunity in Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Min Jiang; Huifang Liu; Zheng Li; Jing Wang; Fengbo Zhang; Kaixiu Cao; Fengsen Li; Jianbing Ding (Hindawi Limited, 2019)
To investigate the effect of ILC2s on Th2-type adaptive immunity during the acute exacerbation of chronic obstructive pulmonary disease (AECOPD), the study enrolled healthy people, stable COPD patients, and AECOPD patients. Flow cytometry was used to detect Th1, Th2, and ILC2 in the peripheral blood and CD80 and MHC II levels on ILC2. The mRNA levels of GATA3, RORα, and CRTH2 of ILC2s were detected by RT-PCR. In addition, ILC2s from the peripheral blood of AECOPD patients were cocultured with CD4+ T cells from the peripheral blood of healthy controls. Cytokine levels in serum of the three groups and the in vitro coculture supernatants were measured by ELISA. Compared with the stable COPD group or the healthy control group, Th2 in the peripheral blood of AECOPD group increased dramatically, inducing an increase of Th2/Th1 ratio in AECOPD patients. Meanwhile, the level of IL-4 in the serum of this group was also increased. However, we also detected ILC2s in the peripheral blood of the AECOPD group and found that it was also increased, alone with the increased GATA3, RORα, and CRTH2 mRNA levels. We also found that the CD80 and MHC II on ILC2 were significantly upregulated and the proportion of MHC II+ ILC2 cells was significantly positively correlated with the proportion of Th2 cells in AECOPD patients. To further demonstrate the effect of ILC2 on Th2 cells, we cocultured ILC2 with CD4+ T cells in vitro, which also showed a significant increase of Th2 ratio as well as Th2-associated cytokines IL-4, IL-5, and IL-13. However, we found that this effect of ILC2s on Th2 cells could be inhibited by the addition of anti-MHC II. The Th2/Th1 balance shifts to Th2 in AECOPD. ILC2s may function as APC by the upregulation of MHC II and regulate adaptive immunity shift to Th2-type response in AECOPD.